2017
DOI: 10.1016/j.scitotenv.2017.03.097
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of soil incorporation of pre-incubated silica-rich rice residue on soil biogeochemistry and greenhouse gas fluxes under flooding and drying

Abstract: Incorporation of silica-rich rice husk residue into flooded paddy soil decreases arsenic uptake by rice. However, the impact of this practice on soil greenhouse gas (GHG) emissions and elemental cycling is unresolved particularly as amended soils experience recurrent flooding and drying cycles. We evaluated the impact of pre-incubated silica-rich rice residue incorporation to soils on pore water chemistry and soil GHG fluxes (i.e., CO, CH, NO) over a flooding and drying cycle typical of flooded rice cultivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
7
1
Order By: Relevance
“…In case of P, this higher immobilization in the black carbon and ash treatment may be attributed to the higher redox potential during incubation experiments probably due to changes in microbial community or lower microbial activity as a result of lower availability of labile carbon after burning and the potential higher amount of iron minerals formed during burning (see above). Compared to previous studies 9 , 10 , showing a negative effect of rice straw burning (leading to a mixture of ash and charred material) on P mobilization (after application in paddy soils), the data of the present study clearly shows that burning to black carbon leads to a much higher P mobilization compared to ash, which our data suggest for the first time when using rice straw as source material. Hence, burning conditions have a very strong influence on later nutrient availability, when using straw-based amendments, which our data suggest for the first time when using rice straw as source material.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…In case of P, this higher immobilization in the black carbon and ash treatment may be attributed to the higher redox potential during incubation experiments probably due to changes in microbial community or lower microbial activity as a result of lower availability of labile carbon after burning and the potential higher amount of iron minerals formed during burning (see above). Compared to previous studies 9 , 10 , showing a negative effect of rice straw burning (leading to a mixture of ash and charred material) on P mobilization (after application in paddy soils), the data of the present study clearly shows that burning to black carbon leads to a much higher P mobilization compared to ash, which our data suggest for the first time when using rice straw as source material. Hence, burning conditions have a very strong influence on later nutrient availability, when using straw-based amendments, which our data suggest for the first time when using rice straw as source material.…”
Section: Discussioncontrasting
confidence: 69%
“…Depending on burning temperature and completeness of mineralization, black carbon (~350 °C burning temperature), biochar (400 to 700 °C fixed-bed slow pyrolysis) or ash (full oxidation) forms. Numerous studies have shown the release of individual nutrients from either fresh straw (P, Si, sulfide 3 5 ), black carbon (Si, P 6 , 7 ), biochar (Si 8 ), ash (Si, P), or a mixture of ash and charred material (Si, P, Fe, and As 9 , 10 ). Rice straw is more prone to microbial decomposition compared to black carbon or ash, and hence induces a lower redox potential in the paddy soil pore water which promotes mobilization of Fe and P 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice husk contains less arsenic and labile carbon and provides more silicon to soil porewater compared to rice straw which releases more arsenic and less silicon in soil porewater than fresh husk or huskash (Penido et al, 2016). In addition, incorporation of rice husk generates less methane emissions, which is a potential greenhouse gas, from rice paddies than incorporation of straw (Penido et al, 2016;Gutekunst et al, 2017). Therefore, rice husk is advantageous over rice straw as a sustainable solution to mitigate arsenic contamination in rice worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…There are many practices influencing SOC storage in croplands. These include tillage management (in some cases, Powlson et al, 2014); crop rotations and cover crops (Poeplau & Don, 2015); improving crop production through fertilization and irrigation management; selection of high residue yielding crops; crop intensification by removing bare fallow management in a cropping system; application of silica residues to reduce greenhouse gas emissions (Gutekunst, Vargas, & Seyfferth, 2017); and application of organic amendments with manure or biochar.…”
Section: Introductionmentioning
confidence: 99%